Analgesic Mechanisms of Lawsone (2-hydroxy-1,4-naphthoquinone) from Lawsonia inermis: A Comprehensive Review of Cyclooxygenase Modulation and Other Molecular Pain Targets - Megawati, Selvi; Utami, Indah Woro (Sciences of Pharmacy, 2026)
Lawsone (2-hydroxy-1,4-naphthoquinone), the principal naphthoquinone of Lawsonia inermis, has attracted interest as a natural anti-inflammatory/analgesic lead that may offer a safer profile than long-term non-steroidal anti-inflammatory drugs. This structured narrative review synthesises evidence from 14 accessible and highly relevant publications (prioritising 2020 onwards) to clarify the mechanistic basis of its analgesic potential. Direct evidence from preclinical studies indicates that lawsone produces anti-inflammatory and anti-arthritic effects comparable to reference drugs and is associated with improved hepatic and renal markers at effective doses. Mechanistically, two experimentally supported axes predominate: (i) reduced prostaglandin biosynthesis, reflected by significant lowering of serum PGE2 and consistent with COX-2 modulation, and (ii) suppression of NF-κB signalling with downstream reductions in key pro-inflammatory cytokines (TNF-α, IL-1β, IL-6). In contrast, potential modulation of the P2X7 purinergic receptor (P2X7R) remains hypothetical, supported mainly by pharmacological and computational studies of structurally related 1,4-naphthoquinone analogues that bind the P2X7R allosteric pocket and inhibit ATP-driven Ca2+ influx and macropore formation. Overall, the evidence positions lawsone as a promising multi-target preclinical scaffold while highlighting the need for direct P2X7R validation, protein-level pathway confirmation, and translational studies.